2009
DOI: 10.1063/1.3275730
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission and dielectric studies of phase transitions within the morphotropic phase boundary of xPb(Zr1/2Ti1/2)O3-(1−x)Pb(Ni1/3Nb2/3)O3 relaxor ferroelectrics

Abstract: We have carried out a combined acoustic emission(AE) and dielectricpermittivity study of the xPb(Zr1/ 2Ti1/2)O3-(1−x)Pb(Ni1/3Nb2/3)O3relaxor ferroelectric ceramics with compositions x=0.7-0.9 corresponding to its morphotropic phase boundary. Temperatures of all phase transitions occurring on heating are identified accurately by AE, and a direct transition between the low-temperature (rhombohedral) and high-temperature (pseudocubic) relaxor phases is found. The AE peak intensity is generally proportional to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…S OLID solutions between a ferroelectric Pb(Zr 1Àx Ti x )O 3 (PZT) and a relaxor ferroelectric Pb(Ni 1/3 Nb 2/3 )O 3 (PNN), namely PZT-PNN ceramics, have attracted special attention due to their richness in phase transitions within a narrow temperature range, from room temperature to 300°C. [1][2][3] PZT-PNN ceramics have been investigated for the possible application to piezoelectric multilayer actuators due to their high piezoelectric properties. 4,5 The piezoelectric constant, d 33 , increased as the amount of PNN increased, but the T c decreased under the same conditions.…”
Section: Introductionmentioning
confidence: 99%
“…S OLID solutions between a ferroelectric Pb(Zr 1Àx Ti x )O 3 (PZT) and a relaxor ferroelectric Pb(Ni 1/3 Nb 2/3 )O 3 (PNN), namely PZT-PNN ceramics, have attracted special attention due to their richness in phase transitions within a narrow temperature range, from room temperature to 300°C. [1][2][3] PZT-PNN ceramics have been investigated for the possible application to piezoelectric multilayer actuators due to their high piezoelectric properties. 4,5 The piezoelectric constant, d 33 , increased as the amount of PNN increased, but the T c decreased under the same conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Leadbased relaxor ferroelectrics have a general formula of Pb(B 0 B″)O 3 (where B 0 represents Mg 2 þ , Ni 2 þ , Zn 2 þ , Fe 3 þ , Sc 3 þ , In 3 þ , Mn 4 þ , or Sn 4 þ ; and B″ represents Nb 5 þ , Ta 5 þ , Sb 5 þ , or W 6 þ ) [8,9]. Relaxor ferroelectrics Pb(Ni 1/3 Nb 2/3 )O 3 -Pb(Zr,Ti)O 3 (abbreviated as PNN-PZT) have attracted much attention due to their excellent piezoelectric properties since Luff et al reported 0.5Pb (Ni 1/3 Nb 2/3 )O 3 À 0.35PbZrO 3 À 0.15PbTiO 3 ternary system in 1974 [10][11][12][13][14]. Dul'kin et al [11] carried out a combined acoustic emission and dielectric permittivity study of the xPZTÀ (1À x) PNN relaxor ferroelectric ceramics with compositions x¼ 0.7-0.9 corresponding to its morphotropic phase boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Relaxor ferroelectrics Pb(Ni 1/3 Nb 2/3 )O 3 -Pb(Zr,Ti)O 3 (abbreviated as PNN-PZT) have attracted much attention due to their excellent piezoelectric properties since Luff et al reported 0.5Pb (Ni 1/3 Nb 2/3 )O 3 À 0.35PbZrO 3 À 0.15PbTiO 3 ternary system in 1974 [10][11][12][13][14]. Dul'kin et al [11] carried out a combined acoustic emission and dielectric permittivity study of the xPZTÀ (1À x) PNN relaxor ferroelectric ceramics with compositions x¼ 0.7-0.9 corresponding to its morphotropic phase boundary. Du et al [12] reported Fe 2 O 3 doped PNNÀ PZT ceramics with d 33 ¼ 956 pC/N and k p ¼ 0.74.…”
Section: Introductionmentioning
confidence: 99%